Геоекологічні аспекти сталого розвитку Рівненської області - Реміз, Світлана Андріївна; Тарасюк, Ніна Адамівна; Remiz, Svitlana A.; Tarasiuk, Nina A. (Тернопільський національний педагогічний університет ім.Володимира Гнатюка, 2013)
Розглянуто регіональні особливості сталого розвитку України на прикладі Рівненської області. Проведено аналітичний огляд теоретико-методологічних засад вивчення геоекологічної ситуації та сталого розвитку в сучасних умовах. В основі дослідження – геоекологічна складова сталого розвитку, яка визначає динаміку господарського комплексу Рівненщини. З використанням проблемно-індикаторного підходу обґрунтовано критерії аналізу геоекологічної ситуації в умовах сталого розвитку, виділені індикатори прояву стійкого розвитку, обґрунтовано провідну роль природних чинників у формуванні сучасної геоекологічної ситуації в межах Рівненщини.

The regional features of the steady development of Ukraine were examined on the example of the Rivne region. For the purpose of sustainable economic complex of the country is an important study of the regional characteristics of each individual area. In each region, formed a kind of complex interaction of natural, historical, cultural, socioeconomic factors. First, the history of economic development, the transformation of landscape protection, natural resource potential determine the need for a regional sustainable development programs. The analytical review of the theoretical methodological principles of the study of the geoecological situation and the steady development in modern conditions were held. Regional peculiarities preconditions for the transition to sustainable development were investigated. In the basis of the research is the geoecological constituent of the steady development that determines the dynamics of the economic complex of the Rivne region. With the use of the problem-indicatory approach the criteria of the analysis of geoecological situation are reasonable in the conditions of the steady development, the indicators of the steady development were distinguished and the leading role of the natural factors in the formation of the modern geoecological situation within the limits of the Rivne region were thought reasonable and the need to introduce the ideas of sustainable development in the region.
Geoecological aspects of the steady development of Pivne region
Keywords: сталий розвиток; геоекологія; геоекологічна складова; геоекологічні індикатори сталого розвитку; оточуюче середовище; геоекологічна ситуація; steady development; geoecology; geoecological constituent; geoecological indicator steady development; environment; geoecological situation